Keaktifan Belajar Siswa Ditinjau Dari Persepsi Siswa Terhadap Keterampilan Mengajar Guru Dan Fasilitas Belajar Pada Mata Pelajaran Ekonomi Kelas XI SMA Batik 2 Surakarta Tahun Ajaran 2015/2016 - Muktisari, Karida Dwi, Prof. Dr. H. Harsono, SU (2016)
The purpose of this study was to determine: (1) To describe the influence of students' perception regarding the teaching skills of teachers to study subjects Economic activeness in class XI SMA Batik 2 Surakarta academic year 2015/2016. (2) To describe the influence learning facility on Economic activity of learning subjects in class XI SMA Batik 2 Surakarta academic year 2015/2016. (3) To describe the influence of students' perception regarding the teaching skills of teachers and learning facilities to economic activity of learning subjects in class XI SMA Batik 2 Surakarta academic year 2015/2016. This type of research is quantitative. The population in this study is a class XI student of Social Sciences (IS) SMA Batik 2 Surakarta, amounting to 159 students with a sample of 110 students were taken by proportional random sampling technique. The data collection technique using questionnaires that have been tested by validity and reliability testing. Data analysis technique used is multiple regression analysis. Based on the multiple regression analysis obtained the following results; 1) Y = 7.154 + 0,323X1 + 0,329X2. 2) From the results obtained t t test for variables Against Student Perceptions of Teaching Skills Teacher at 5,060 while ttable 1,982. thitung for Learning Facilities variable of 3.612 while ttable 1,982. 3) From the analysis of the F test obtained F count = 34.857> F table = 3.081. Based on the analysis and discussion can be concluded; 1) that the variable Against Student Perceptions of Teachers and Teaching Skills Learning Facility has an effect on the Students' Learning Activeness Subjects Economics. 2) Ho denied that there is significant influence between Student Perceptions of Teaching Skills Teachers Against the liveliness Economic Study Subjects individually. then Ho is rejected so that there is significant influence between the liveliness of Learning Facilities Study Subjects Economics individually. 3) Ho rejected so that together there is significant influence Student Perceptions Of Teaching Skills Teacher (X1), and Learning Facility (X2) to activeness Subjects Student in Economics. Variable X1 gives the relative contribution of 62.7% and the effective contribution of 55%, X2 gives the relative contribution of 37.3% and the effective contribution of 21.1%. The calculation result obtained 0337 R2, meaning 33.7% activity of learning on the subjects of Economics influenced by students 'perceptions of teachers' teaching skills and learning facilities, while the remaining 66.3% influenced by variables outside the research.